Supporting Simultaneous Air Revitalization and Thermal Control in a Crewed Habitat With Temperate Chlorella vulgaris and Eurythermic Antarctic Chlorophyta - Matula, Emily E.; Nabity, James A.; McKnight, Diane M. (Frontiers in Microbiology, 2021)
Including a multifunctional, bioregenerative algal photobioreactor for simultaneous air revitalization and thermal control may aid in carbon loop closure for long-duration surface habitats. However, using water-based algal media as a cabin heat sink may expose the contained culture to a dynamic, low temperature environment. Including psychrotolerant microalgae, native to these temperature regimes, in the photobioreactor may contribute to system stability. This paper assesses the impact of a cycled temperature environment, reflective of spacecraft thermal loops, to the oxygen provision capability of temperate Chlorella vulgaris and eurythermic Antarctic Chlorophyta. The tested 28-minute temperature cycles reflected the internal thermal control loops of the International Space Station (C. vulgaris, 9 C to 27 C; Chlorophyta-Ant, 4 C to 14 C) and included a constant temperature control (10 C). Both sample types of the cycled temperature condition concluded with increased oxygen production rates (C. vulgaris; initial: 0.013 mgO2 L-1 , final: 3.15 mgO2 L-1 and Chlorophyta-Ant; initial: 0.653 mgO2 L-1, final: 1.03 mgO2 L-1) and culture growth, suggesting environmental acclimation. Antarctic sample conditions exhibited increases or sustainment of oxygen production rates normalized by biomass dry weight, while both C. vulgaris sample conditions decreased oxygen production per biomass. However, even with the temperature-induced reduction, cycled temperature C. vulgaris had a significantly higher normalized oxygen production rate than Antarctic Chlorophyta. Chlorophyll fluorometry measurements showed that the cycled temperature conditions did not overly stress both sample types (FV/FM: 0.6-0.75), but the Antarctic Chlorophyta sample had significantly higher fluorometry readings than its C. vulgaris counterpart (F = 6.26, P < 0.05). The steady state C. vulgaris condition had significantly lower fluorometry readings than all other conditions (FV/FM: 0.34), suggesting a stressed culture. This study compares the results to similar experiments conducted in steady state or diurnally cycled temperature conditions. Recommendations for surface system implementation are based off the presented results. The preliminary findings imply that both C. vulgaris and Antarctic Chlorophyta can withstand the dynamic temperature environment reflective of a thermal control loop and these data can be used for future design models.